2021
DOI: 10.1111/iju.14737
|View full text |Cite
|
Sign up to set email alerts
|

Holmium laser enucleation versus bipolar resection in the management of large‐volume benign prostatic hyperplasia: A randomized controlled trial

Abstract: Abbreviations & Acronyms AC/AP = anticoagulants/ antiplatelets BPH = benign prostatic hyperplasia B-TURP = bipolar transurethral resection of prostate CI = confidence interval Hb = hemoglobin HoLEP = holmium laser enucleation of the prostate IPSS = International Prostate Symptom Score LUTS = lower urinary tract symptoms MMM = morcellator/machine malfunction M-TURP = monopolar transurethral resection of the prostate OR = odds ratio PSA = prostate-specific antigen PVRU = post-void residual urine Q max = maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…A total of 449 articles were searched in the database, and there were only 57 articles left after reading the title and abstract. By reviewing the full-text articles and qualitative synthesis, 11 studies were finally included in our meta-analysis ( Elshal et al, 2020 ; Fuschi et al, 2021 ; Ghobrial et al, 2021 ; Guo, 2020 ; Habib et al, 2020 , 2022 ; Higazy et al, 2021 ; Kuntz et al, 2004 , 2008 ; Kuntz & Lehrich, 2002 ; J. Zhang et al, 2020 ). The details of included studies were presented in Figure 1 , and the characteristics and baseline are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 449 articles were searched in the database, and there were only 57 articles left after reading the title and abstract. By reviewing the full-text articles and qualitative synthesis, 11 studies were finally included in our meta-analysis ( Elshal et al, 2020 ; Fuschi et al, 2021 ; Ghobrial et al, 2021 ; Guo, 2020 ; Habib et al, 2020 , 2022 ; Higazy et al, 2021 ; Kuntz et al, 2004 , 2008 ; Kuntz & Lehrich, 2002 ; J. Zhang et al, 2020 ). The details of included studies were presented in Figure 1 , and the characteristics and baseline are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…RCTs of GreenLight and HoLEP versus TURP report significant benefits with the laser treatments in terms of catheterisation time and hospital length of stay. 23 , 24 GreenLight is also shown to have significantly lower perioperative bleeding compared to TURP, 23 while HoLEP does not but does have significantly shorter operative time compared to TURP. 24 Similar results have been reported for HoLEP versus bipolar enucleation, 25 and bipolar enucleation has been shown to be superior to bTURP with respect to operative time, catheterisation time, postoperative bleeding complications and bladder neck contracture.…”
Section: Discussionmentioning
confidence: 97%
“…Most studies reported shorter hospitalization durations with PVP, ThuVARP, DiLEP, and HoLEP than with TURP [ 24 , 25 , 26 , 27 ]. Some smaller studies reported no significant differences in hospitalization duration between HoLEP and B-TURP [ 25 , 28 ]. Our study revealed significantly shorter hospitalization durations with PVP, ThuVARP, and DiLEP than with M-TURP but not with HoLEP and B-TURP.…”
Section: Discussionmentioning
confidence: 99%